Waste Rock Geochemistry as an aid to the Development of Cost-Effective Mine Waste Planning and Rehabilitation Strategies (The Australasian Institute of Mining and Metallurgy, 1993)
The geochemistry of waste rock from mining operations is critical to the development of acidity-related environmental problems during mining operations, and following mine closure. Failure to recognise the potential for waste rock to produce acidic oxidation products may cause mobilisation of heavy metals into ground and surface waters, and create heavy metal levels in soils which are toxic to plants, causing the failure of revegetation programs. Although more usually associated with wet tropical environments, the potential exists for these problems to occur even in and regions such as the Eastern Goldfields region of Western Australia unless appropriate pre-planning is undertaken.Acidity-related mine waste problems can be extremely expensive to rectify, but can be avoided by waste rock characterisation, and pre-planning of waste rock deposition based on this information. Integration of knowledge of waste rock geochemistry with geotechnical engineering, and application to likely problems, is essential for the successful planning and implementation of cost-effective strategies to avoid problems occurring. Pre-planning to avoid problems is likely to be significantly less expensive in most cases than remedial actions to rectify problems after they have occurred, and in fact may involve no additional cost if it requires only rescheduling or redesign of existing or planned Activities.